Teaching internship and PIBID: an experience of initial training of literacy teachers (Research, Society and Development, 2022)
The present article intends to impart a teaching experience developed throughout training actions with undergraduate students of Pedagogy course who are members of the Institutional Program Initiation of Scholarship to Teaching (PIBID), in 2019, seeking the initial training of literacy teachers. It was carried out three training meetings, fortnightly, based on the theoretical framework of authors who discuss the relationship of interdependence and inseparability between the processes of al alphabetization and literacy. The unfolding of these activities occurred as follows: initially by explanations and reflections of the concepts of alphabetization and literacy, followed by the demonstration of a didactic sequence with the objective of learning written language and, finally, the elaboration by the undergraduate students of another didactic sequence with the same purpose. Our meetings resulted in this didactic product, which was organized as a booklet for the use and assistance of undergraduate students in the process of teaching and learning the written language of children who are in the beginning of elementary school. In view of all the work carried out, the relevance of the development of experiences, involving teaching, research and extension, to strengthen the initial training of teachers able to teach Brazilian children to write and read, and to use these skills in the most diverse situations of the daily life.